2021
DOI: 10.3389/fphar.2020.622046
|View full text |Cite
|
Sign up to set email alerts
|

Emodin Inhibits the Proliferation of MCF-7 Human Breast Cancer Cells Through Activation of Aryl Hydrocarbon Receptor (AhR)

Abstract: Natural products have proved to be a promising source for the development of potential anticancer drugs. Emodin, a natural compound from Rheum palmatum, is used to treat several types of cancers, including lung, liver, and pancreatic. However, there are few reports regarding its use in the treatment of breast cancer. Thus, the therapeutic effect and mechanism of emodin on MCF-7 human breast cancer cells were investigated in this study. Morphological observations and cell viability were evaluated to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…Rhubarb is also named dahuang in China. Rhubarb also contains many active constituents with pharmacological activities such as rhein, emodin, and danthron ( Xian et al, 2020 ; Zhang N. et al, 2020 ; Ma et al, 2021 ). Rhein is the main active constituent of Rhubarb with pharmacological activity.…”
Section: Discussionmentioning
confidence: 99%
“…Rhubarb is also named dahuang in China. Rhubarb also contains many active constituents with pharmacological activities such as rhein, emodin, and danthron ( Xian et al, 2020 ; Zhang N. et al, 2020 ; Ma et al, 2021 ). Rhein is the main active constituent of Rhubarb with pharmacological activity.…”
Section: Discussionmentioning
confidence: 99%
“…found that emodin is an effective aromatic hydrocarbon receptor (AhR) agonist. Subsequent in vitro experiments also found that the expression levels of AhR and cytochrome P450 1A1 (CYP1A1) in MCF-7 cells were significantly upregulated by emodin treatment, suggesting that the antitumor effects of emodin against BC might be related to the AhR-CYP1A1 signaling pathway 120 .…”
Section: Anticancer Effects Of Emodinmentioning
confidence: 97%
“…The effect of emodin on cell proliferation was studied and confirmed for many cancer cell lines, including breast [40], skin [41], pancreas [42], colon [43,44], ovarian [45], prostate [46], esophageal [47], bladder [48], and endometrial [49]. For example, the IC50 values for MCF-7 (breast) and HepG2 (liver) cancer cells were 52.72 μM and 43.87 μM, respectively [50].…”
Section: Proliferationmentioning
confidence: 98%